Immersive virtual reality for learning exoskeleton-like virtual walking: a feasibility study - Rodríguez-Fernández, Antonio; den Berg, Alex van; Cucinella, Salvatore Luca; Lobo-Prat, Joan; Font-Llagunes, Josep M.; Marchal-Crespo, Laura (Journal of NeuroEngineering and Rehabilitation, 2024)
Virtual Reality (VR) has proven to be an effective tool for motor (re)learning. Furthermore, with the current commercialization of low-cost head-mounted displays (HMDs), immersive virtual reality (IVR) has become a viable rehabilitation tool. Nonetheless, it is still an open question how immersive virtual environments should be designed to enhance motor learning, especially to support the learning of complex motor tasks. An example of such a complex task is triggering steps while wearing lower-limb exoskeletons as it requires the learning of several sub-tasks, e.g., shifting the weight from one leg to the other, keeping the trunk upright, and initiating steps. This study aims to find the necessary elements in VR to promote motor learning of complex virtual gait tasks.